Perencanaan Penghapusan Piutang Pajak Bumi dan Bangunan Perdesaan dan Perkotaan di Badan Pendapatan Daerah Kota Bandung - Mega Fitri Halimah; Suryanto, Suryanto (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
This research was motivated by the high number of PBB-P2 receivables in Bandung City. Based on the high amount of PBB-P2 receivables, the Bandung City Regional Revenue Agency as the tax manager needs to treat this incident. The treatment that can be carried out is to write off PBB-P2 receivables. It is necessary to write off PBB-P2 receivables because they have a burden on regional financial balance sheets. The receivables appear to be collectible even though the collection rate is already low. Before implementing this policy, the Regional Revenue Agency must carry out planning first. Therefore, this research aims to explain the planning for writing off PBB-P2 receivables by the Bandung City Regional Revenue Agency by analyzing it using 5 stages of the planning process, namely problem identification, data collection, data analysis, choosing the method that looks best, and implementation. .The research method used is descriptive with a qualitative approach. The data collection techniques used were observation, interviews and literature study. The data analysis technique applied is data collection. Data reduction, data presentation, and drawing conclusions. The research results show that the planning for writing off PBB-P2 receivables has not gone completely well because of the 5 stages there are 2 stages that are not fully in accordance with the research theory used. In this way, it is hoped that the Bandung City Regional Revenue Agency can complete and complete the required data and set a time target for an activity.